De pilón Studi traduttologici, linguistici e letterari su America Latina e Caraibi - Secci, Maria Cristina (Tertulias, 2020)
Divided into three sections, it hosts contributions on translation, literature and language in Latin America. "Mediation, Writing and Society" is built around reflection on the cultural and social application of the mediation network and the origin of the creative process from forays into the writer's worktable. "Literature and Plot" explores the theme of warp in a cultural, historical, and personal point of view, while "Translation and Practice" concerns the experiential application of this discipline.